Prenuptial Agreement and Exclusion of Indissolubility of Marriage - Wolczko, Marcin; Zawiślak, Karol (Prawo Kanoniczne, 2025)
The paper presents the provisions of Polish law regarding the matrimonial property regime of spouses and the possibility of concluding an agreement establishing the separation of property, indicating its effects, including positive ones, in relation to the spouses' obligation to meet the material needs of the family. In the part referring to canon law, it is shown that the mere signing of a prenuptial agreement does not constitute the exclusion of the indissolubility of marriage. The Church adopts a neutral stance on the issue of the matrimonial property regime, leaving spouses the freedom to choose and shape it.